Advantages and disadvantages of unstructured cardiovascular risk factor screening for follow-up in primary care. (29th August 2020) - de Boer, Anna W; de Mutsert, Renée; den Heijer, Martin; Rosendaal, Frits R; Jukema, Johan W; Blom, Jeanet W; Numans, Mattijs E
Abstract: Background: In contrast to structured, integrated risk assessment in primary care, unstructured risk factor screening outside primary care and corresponding recommendations to consult a general practitioner (GP) are often based on one abnormal value of a single risk factor. This study investigates the advantages and disadvantages of unstructured screening of blood pressure and cholesterol outside primary care. Methods: After the baseline visit of the Netherlands Epidemiology of Obesity study (population-based prospective cohort study in persons aged 45–65 years, recruited 2008–2012) all participants received a letter with results of blood pressure and cholesterol, and a recommendation to consult a GP if results were abnormal. Four years after the start of the study, participants received a questionnaire about the follow-up of their results. Results: The study population consisted of 6343 participants, 48% men, mean age 56 years, mean body mass index 30 kg/m 2 . Of all participants 66% had an abnormal result and, of these, 49% had a treatment indication based on the risk estimation system SCORE-NL 2006. Of the 25% of the participants who did not consult a GP, 40% had a treatment indication. Of the participants with an abnormal result 19% were worried, of whom 60% had no treatment indication. Conclusions: In this population 51% of the participants with an abnormal result had unnecessarily received a recommendation to consult a GP, and 10% were unnecessarily worried. GPs should be informed about the complete risk assessment, and only participants at intermediate or high risk should receive a recommendation to consult a GP.